Albania : Poverty Reduction Strategy Paper-Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
This paper reviews the progress report on implementation of the National Strategy for Socio-Economic Development (NSSED) during 2004 in Albania. The NSSED established a multiyear plan to combat poverty and strengthen governance. The main implication of the Integrated Planning System for the NSSED is that it will evolve into a comprehensive strategic planning framework. Its focus will accordingly shift toward medium to long-term planning, ensuring that a coherent, costed, mutually consistent sector and cross-cutting strategies are developed that serve as the policy basis for the annual Medium-Term Budget Program process.